CpG Oligodeoxynucleotides Protect Normal and SIV-Infected Macaques from Leishmania Infection - Verthelyi, Daniela; Gursel, Mayda; Kenney, Richard T; Lifson, Jeffrey D; Liu, Shuying; Mican, Joan; Klinman, Dennis M (The Journal of immunology (1950), 2003)
Oligodeoxynucleotides containing CpG motifs (CpG ODNs) mimic microbial DNA and activate effectors of the innate immune response, which limits the spread of pathogens and promotes an adaptive immune response. CpG ODNs have been shown to protect mice from infection with intracellular pathogens. Unfortunately, CpG motifs that optimally stimulate humans are only weakly active in mice, mandating the use of nonhuman primates to monitor the activity and safety of “human” CpG ODNs in vivo. This study demonstrates that CpG ODN treatment of rhesus macaques significantly reduces the severity of the lesions caused by a challenge with Leishmania. Leishmania superinfection is common in immunocompromised hosts, particularly those infected with HIV. This study shows that PBMCs from HIV-infected subjects respond to stimulation with CpG ODNs. To determine whether CpG ODNs can protect retrovirus-infected primates, SIV-infected macaques were treated with CpG ODNs and then challenged with Leishmania. Both lesion size and parasite load were significantly reduced in the CpG-treated animals. These findings support the clinical development of CpG ODNs as immunoprotective agents in normal and HIV-infected patients.